Building on Its Past: The Future of Business and Society Scholarship. Issue 5 (May 2022) - Brown, Jill A.; de Bakker, Frank G. A.; Bapuji, Hari; Higgins, Colin; Rehbein, Kathleen; Spicer, Andrew
This Special Issue commemorates the 60th anniversary of Business & Society with nine rigorous literature reviews that address important societal problems and provide opportunities for theory development in the business and society field; in this introduction we present an overview of the Special Issue. With the theme "Building on Its Past, " the nine articles address a host of contemporary issues, including climate change, wicked problems, business and human rights, human health, certifications standards, the governance of artificial intelligence, stakeholder engagement, stakeholder theory, and corporate political activity. Together, these reviews offer a wealth of suggested themes, theories and approaches that can drive our research forward for the next decades in business and society research and practice. Using the lens of a miner-prospector continuum to categorize the diversity of articles within this special issue, a common theme emerges across the portfolio of reviews: they all call for a more systemic and integrative perspective toward studying the complex interactions that link business and society actors and issues. Building on these findings, we encourage future scholars to fill long-standing researched gaps through a more open systems approach, which supports both contextually sensitive and multi-level and multi-disciplinary approaches to address grand societal challenges. We conclude with specific suggestions as to how business and society scholars might use an open systems approach, including embracing methodologies to address complex causal pathways, theorizing with a view towards spanning external and internal elements of an organization, and reflecting on the temporal and spatial dynamics of complex systems.